Recovering from conflict : strategy for an international response - Forman, Shepard (Centre on International Cooperation New YorkUS)
Identifies seven challenges that the international aid community must address to maximize its support for sustainable peace and reconstruction in the wake of conflict. Calls for stricter collaboration in designing aid interventions; mobilizing resources; deepening institutional reform; harmonizing aid conditions; coordinating assistance locally; enhancing recipient capacities; and, ensuring accountability in aid delivery and implementation. Recommends institutionalizing these efforts in a new Strategic Recovery Facility that would ensure the timely disbursement of aid in a more coherent and equitable manner.